Evaluation of tree trunk shapes in experimental cultures of the European North of Russia - Y. M. Avdeev; S. M. Khamitova; A. E. Kostin; P. A. Shvetsov (Новые технологии)
The article is devoted to assessing the shape of tree trunks in experimental forest crops in the Vologda region. Experimental cultures are of considerable theoretical and practical interest. Shapes of trunks in the forest cultures of the Northern European Russia have not been investigated. The article presents data on the q2 form coefficient in the experimental forest cultures of spruce fir. A comparative assessment of the shape of trunks in plantations created by different methods and with the use of different types of agrotechnical and forestry care has been made. Correlations between the form and other parameters of tree trunks are revealed. The results can be used to replenish data on the shape of tree trunks in forest crops, to clarify and understand the processes in cultures of this age, to simplify the procedure for the selection of high-quality tree trunks for q2.